Flufenoxuron, an acylurea insect growth regulator, alters development of Tribolium castaneum (Herbst) (Coleoptera :tenebrionidae) by modulating levels of chitin, soluble protein content, and HSP70 and p34(cdc2) in the larval tissues - Salokhe, S.; Sarkar, A.; Kulkarni, A.; Mukherjee, Samindra N.; Pal, J. K. (Pesticide Biochemistry and Physiology, 2006)
The effect of sublethal concentrations, 0.00141% (LC20), 0.00251% (LC30), and 0.0036% (LC40) of a dispersible formulation of an acylurea insect growth regulator, flufenoxuron (Cascade) on certain biochemical parameters in the larvae of Tribolium castaneum was investigated. When neonates were fed on diet treated with sublethal concentrations for 24 It, it was observed that at all concentrations tested, there was a significant reduction in chitin content on the 15th day of development. Total soluble protein content at LC20 and LC30 decreased with increasing age of the larvae. At LC20 and LC40 concentrations there was a progressive increase in the protein: chitin ratio as a function of increase in age of the larvae. SDS-PAGE analysis of the larval tissue extracts indicated gross quantitative changes in some of the protein bands (MW 50-97 kDa). Western blot analysis revealed significant increase in the level of HSP70 in the extracts of larvae fed on LC30 treated diet, on the 7th and 10th day of development in the decreasing order. Conversely, a significant decrease in the hyper-phosphorylated form of p34(cdc2) kinase due to flufenoxuron treatment indicating modulation of cell cycle regulation was observed. Thus, sublethal concentrations of flufenoxuron alter expression of developmentally regulated proteins, HSP70 and p34(cdc2) and chitin formation in a stage-specific manner thereby resulting developmental abnormalities in T castaneum. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: chitin; Development; flufenoxuron; HSP70; p34(cdc2); phosphotyrosine; sublethal effects; total soluble proteins; Tribolium castaneum

Subcritical water hydrolysis of N-acetyl-D-glucosamine: hydrolysis mechanism, reaction pathways and optimization for selective production of 5-HMF and levulinic acid - Kulkarni, Sphurti Prakash; Dure, Shital N.; Joshi, Sunil S.; V. Pandare, Kiran; Mali, Nilesh A. (Carbohydrate Research, 2022)
In this study, the subcritical water hydrolysis of N-acetyl-D-glucosamine (NAG), a monomer of abundant renewable marine biopolymer chitin, for production of value-added chemicals is investigated. The enhanced ionization of water at subcritical conditions (200 degrees C; 50-100 bar), provides enough acidity for deacetylation of NAG resulting in 80% yield of acetic acid along with traces of formic acid, lactic acid, glucose, fructose, 5hydroxymethylfurfural (5-HMF),etc. The significant humin formation indicates that the self-condensation and polymerisation of 5-HMF is favored in water at subcritical conditions. A catalyst p-toluenesulfonic acid (p-TsOH) was employed to selectively convert NAG to levulinic acid (LA) via ring opening of 5-HMF previously formed during hydrolysis. The maximum yield of 27.13 +/- 1% and 53.46 +/- 1% of 5-HMF and LA, respectively, was obtained at process conditions optimized using Box-Behnken design coupled with response surface methodology. Subcritical water enables greener conversion of NAG to platform chemicals wherein the selective production can be achieved by tuning the process conditions.
Keywords: 5-Hydroxymethylfurfural; chitin; Glucosamine; levulinic acid; Response surface methodology; Subcritical water